The curriculum in tension. A discussion of universalism and particularism - Southwell, Myriam Monica (2016)
This article will integrate a certain historical approach seeking to question the most outstanding elements on which the discourse of inclusion in our region was built. It will also explore how the institutional concretions of the story of inclusion are being increasingly stressed and called into question. Finally, we will seek to raise the discussion of “school format” in contemporary society and in the face of the imperatives of school expansion and adaptation to the demands of social movements. We will do this analysis from the conceptual tension between universalism and particularism.